Hydrocarbons and methylotrophy - Lidstrom, Mary E. (Methods in enzymology, 1990)
This volume is the first comprehensive compilation of methods for the assay and purification of enzymes involved in the utilization of reduced one-carbon compounds and higher hydrocarbons. In the last decade there has been an explosion of interest in the organisms that grow on one-carbon compounds and in those that grow on higher hydrocarbons. This is due to the commercial interest in the unique enzymes involved in these specialty metabolic pathways and to a growing understanding of the important role these organisms play in carbon cycling in nature. More recent interest in the use of these organisms and their enzymes for detoxification of hazardous waste has once again put the spotlight on these unique microorganisms. This volume will prove to be a valuable source for researchers in academia, government, and industry alike.